Overview of Crosstalk Between Multiple Factor of Transcytosis in Blood Brain Barrier - Tjakra, Marco; Wang, Yeqi; Vania, Vicki; Hou, Zhengjun; Durkan, Colm; Wang, Nan; Wang, Guixue (Frontiers in Neuroscience, 2020)
Blood brain barrier (BBB) conserves unique regulatory system to maintain barrier tightness while allowing adequate transport between neurovascular units. This mechanism possess a challenge for drug delivery, while abnormality may result in pathogenesis. Communication between vascular and neural system is mediated through paracellular and transcellular (transcytosis) pathway. Transcytosis itself showed dependency with various components, focusing on caveolae-mediated. Among several factors, intense communication between endothelial cells, pericytes, and astrocytes is the key for a normal development. Regulatory signaling pathway such as VEGF, Notch, S1P, PDGFβ, Ang/Tie, and TGF-β showed interaction with the transcytosis steps. Recent discoveries showed exploration of various factors which has been proven to interact with one of the process of transcytosis, either endocytosis, endosomal rearrangement, or exocytosis. As well as providing a hypothetical regulatory pathway between each factors, specifically miRNA, mechanical stress, various cytokines, physicochemical, basement membrane and junctions remodelling, and crosstalk between developmental regulatory pathways. Finally, various hypotheses and probable crosstalk between each factors will be expressed, to point out relevant research application (Drug therapy design and BBB-on-a-chip) and unexplored terrain.